2014
DOI: 10.1073/pnas.1317505111
|View full text |Cite
|
Sign up to set email alerts
|

Gaining trust as well as respect in communicating to motivated audiences about science topics

Abstract: Expertise is a prerequisite for communicator credibility, entailing the knowledge and ability to be accurate. Trust also is essential to communicator credibility. Audiences view trustworthiness as the motivation to be truthful. Identifying whom to trust follows systematic principles. People decide quickly another’s apparent intent: Who is friend or foe, on their side or not, or a cooperator or competitor. Those seemingly on their side are deemed warm (friendly, trustworthy). People then decide whether the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
319
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(330 citation statements)
references
References 36 publications
(34 reference statements)
11
319
0
Order By: Relevance
“…Factors like perceived trustworthiness, reputation, values, political leanings, age, gender, educational background, and personal risk tolerance all have an effect on people's perceptions of a speaker and their message (Fiske and Dupree 2014). High-quality journals such as Public Understanding of Science (pus.sagepub.com/) and Science Communication (scx.sagepub.com/) offer a wealth of conceptual and empirical insight into the effectiveness of different techniques.…”
Section: Understand the Science Of Science Communicationmentioning
confidence: 99%
“…Factors like perceived trustworthiness, reputation, values, political leanings, age, gender, educational background, and personal risk tolerance all have an effect on people's perceptions of a speaker and their message (Fiske and Dupree 2014). High-quality journals such as Public Understanding of Science (pus.sagepub.com/) and Science Communication (scx.sagepub.com/) offer a wealth of conceptual and empirical insight into the effectiveness of different techniques.…”
Section: Understand the Science Of Science Communicationmentioning
confidence: 99%
“…It also demands resources for the direct costs of analysis, elicitation, and message development, and for the opportunity costs of having scientists spend time communicating uncertainty rather than reducing it (through their research). Making this investment means treating communication as part of scientists' professional responsibility and rewarding them for strengthening the public goodwill that science needs (40). This investment would be more attractive if it advanced science, as well as making it more useful.…”
Section: Resultsmentioning
confidence: 99%
“…Even when people recognize those problems, they may be insufficiently sensitive, as seen in biases such as the base-rate fallacy, belief in the law of small numbers, and insufficiently regressive predictions (37). When uncertainties arise from limits to the science, decision makers must rely on the community of scientists to discover and share problems, so as to preserve the commons of trust that it enjoys (40).…”
mentioning
confidence: 99%
“…Communicator credibility depends on status and expertise on the one hand and on affectionately ascribed trustworthiness on the other. For the US it has been shown that professors are ascribed both, expertise and trustworthiness (Fiske and Dupree 2014). This gives them an excellent initial position as communicators for people will tend to believe them and agree with their opinions.…”
Section: The Challenge Of Creating Proper Understanding Of Sustainablmentioning
confidence: 99%